RESEARCH OF PROCESSES OF FORMATION POLLUTION AREARS IN ATMOSPHERE NEAR COMPRESSOR STATIONS OF TRUNK GAS PIPELINES - Semchuk, Y. M.; Lialiuk-Viter, H. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
In the article analyzes the formation of areas of atmosphere pollution which caused by the compressor stations of main gas pipelines. The main dangerous factors in the zone of influence of CS, which have affect on the natural environment, is the chemical pollution of atmosphere due to emissions of harmful substances by technological equipment CS and noisiness, the source of which are gas pumping units of different types. In the atmospheric pollution, there are 3 zones: 1) zone of "undiluted" concentrations; 2)transitional zone; 3) dispersed zones. Essential processes of migration of air pollution are convective transfer, dispersion and molecular diffusion. Also, in the article are given the methods of calculating of the concentrations of harmful substances and estimation of the levels of air pollution in the area of the compressor station location. The main directions of reduction of the influence of CS on the environment are proposed, in particular: replacement of obsolete gas-pumping units with new ones; improvement of technological equipment; optimization of parameters of operation of gas turbine plants (GTU); the transfer of separate workshops (or CS as a whole) to electric power; reduction of ecological load on gas-pumping units (GPA); increase in the height of the smoke pipes; using secondary energy resources in the implementation of energy saving equipment and systems, etc.